5 - The Politics of Marginal Forms: Popular Music, Cultural Identity and Political Opposition in Kenya: DOI: 10.4314/ad.v29i4.22208 - WEKESA, Peter Wafula (Africa Development, 2004)
In the contemporary world, discourse on global cultural flows and related outcomes has moved to the center stage in scholarly research and activist realms. In this discourse, especially that related to fundamental world views on globalization and to the links between different communities of the world, the space that popular music occupies is very central. This is because popular music has always subverted the notion of national boundaries, transcended and transformed them into new conduits and spaces that allow for the emergence of new identities. While there is nothing particularly new about the foregoing global trend, its significance in cultural and political debates, at least in Africa and Kenya in particular, has scarcely been appreciated. Little attention has been paid by scholars to an interesting dimension of popular music as a means of making history, interpreting reality and also as a medium that is directed at transforming the present reality in order to realize a better future for the people. At best scholars have treated popular music merely as a debased culture produced only for entertainment and whose aim is to render the audience passive and mindless in the corporate search for the lowest common denominator of acceptability and appreciation. This paper focuses specifically on the Kenyan context to contest the foregoing position. Its argument rests on the axiom that whereas it has become normal in the writings on civil society, democratization and so on, to emphasize forms of cultural expressions that are perceived to be avowedly more understood in political circles than others, the space of popular music cannot be under-estimated. It is beneath the dialectics of production and consumption of this popular music with all its contradictions that the fertile intellec marginalization could be resuscitated. The paper, addres a historical perspective, takes into account its dynamic in experience, social practice, individual and cultural expr creatively adapting to perceived material conditions t vital role of popular music as a system for the enact emergent patterns of identity under conditions of per economic change.